Pengembangan Implementasi Gerakan Literasi Sastra Anak Mampukah Menumbuhkan Minat Baca Siswa Sekolah Dasar? - Muh. Arafik; Titis Angga Rini (Faculty of Education Universitas Negeri Malang, 2021)
Abstract: The low reading interest of elementary school students in Indonesia needs serious attention. The various obstacles behind it must be immediately found a solution. Starting from the problem of availability of reading sources and uneven distribution, the role of family and community support, to the effectiveness of children’s literary literacy development programs in elementary schools. This study aims to identify, describe and interpret in depth all activities of the Children’s Literacy Movement (CLM) at the development stage in order to foster reading interest in elementary school students. This study used a qualitative approach with case study design. Instruments of data collection were conducted through interviews, observations, and documentation studies. The data analysis technique used is descriptive qualitative. The results showed that CLM activities at the development stage were carried out through activities (1) children’s literary literacy bags, (2) mandatory library visits, (3) independent reading of literature child. Various activities for developing children’s literary literacy in schools will develop if there is support for similar activities carried out by families and the community. Reading pleasure through children’s literature can foster students’ interest in reading. Abstrak: Rendahnya minat baca siswa sekolah dasar di Indonesia perlu mendapatkan perhatian yang serius. Berbagai hambatan yang melatarbelakanginya harus segera dicarikan solusinya. Mulai dari permasalahan ketersediaan sumber bacaan dan persebaran yang belum merata, peran keluarga dan dukungan masyarakat, sampai dengan efektifitas program pengembangan literasi sastra anak di sekolah dasar. Penelitian ini bertujuan untuk mengidentifikasi, mendeskripsikaan dan memaknai secara mendalam semua aktivitas Gerakan Literasi Sastra Anak (GLSA) pada tahap pengembangan guna menumbuhkan minat baca siswa sekolah dasar. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Instrumen pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Teknik analisis data yang digunakan adalah deskriptif kualitatif. Hasil penelitian menunjukkan aktivitas GLSA pada tahapan pengembangan dilakukan melalui kegiatan (1) gebyar literasi sastra anak, (2) kantong literasi sastra anak, (3) wajib kunjung perpustakaan, (4) membaca mandiri sastra anak. Beragam aktivitas pengembangan literasi sastra anak disekolah akan berkembang jika ada dukungan kegiatan serupa yang dilakukan keluaraga dan masyarakat. Membaca kesenangan melalui buku-buku sastra anak mampu menumbuhkan minat baca siswa.